Familial olivopontocerebellar atrophy with neonatal onset: a recessively inherited syndrome with systemic and biochemical abnormalities. - Harding, B N (1988)
Clinical and pathological findings are reported in two siblings who presented in the neonatal period with failure to thrive, hypotonia, pericardial effusions, limitation of joint movement, retinal dystrophy and loss of visual function. Additional features were biochemical evidence of purine overproduction and liver dysfunction. Post mortem, the neuropathological findings in both children were typical of olivopontocerebellar atrophy. It is suggested that the cases represent a recessively inherited inborn error of metabolism.